(untitled) (Sudurpaschim Spectrum, 2023)
This paper aims to discuss the emerging trend and scope of Development Studies as an academic discipline. Methodologically, the paper is based on secondary sources of data. A comparative and argumentative method has been followed in a continuum approach to Rural Development and Development Studies. It argues that conventional particularistic approaches to development are being upgraded in the more general domain of Development Studies. Therefore, going with some national and international trends of studies in both disciplines, this paper offers a strong recommendation for the adoption of Development Studies with exploration and extended continuity of Rural Development. The paper does not, however, conclude with the immortality of the discipline of Development Studies but stands with its continuous evolution and contestation. Taking the reference of Nepal, the paper has highlighted different issues, opportunities, and challenges of such shifting in terms of quality of the program, courses and faculties, career and exposure, and research potential and policy dilemma. The paper is expected to contribute to the studies of different paradigms and discourses of development in their given contexts and conditions of socio-political realties.